Pulmonary epithelial‐myoepithelial carcinoma (P‐EMC) with focal high grade transformation: Molecular and cytologic findings. Issue 6 (31st January 2022) - Charles, River; Murray, Sarah; Gray, Eric; Hu, Jingjing
Abstract: Background: Pulmonary epithelial‐myoepithelial carcinoma (P‐EMC) is a rare type of salivary gland tumor of the lung. Diagnosis from preoperative biopsies or fine needle aspiration (FNA) cytology specimens is difficult given the rarity of the tumor and overlapping cytomorphology with other entities. These tumors generally have a good prognosis, however prior reports of recurrence and metastasis to lymph nodes have been reported. Further, little is known about the malignant potential of high grade transformation. The molecular characteristics of this entity are unknown, with only a few case reports commenting on molecular findings. Here, we report a case of P‐EMC with focal high grade transformation. We present its diagnostic pitfalls on cytology specimens, surgical pathology, immunohistochemistry, and molecular findings. Case presentation: A 72 year old female presented with an incidentally detected lung mass. A chest computed tomography (CT) demonstrated a left hilar mass measuring 4.1 cm with endobronchial extension into the left upper lobe. On the initial endobronchial core needle biopsy and cytology FNA, the tumor was misinterpreted as squamous cell carcinoma. The patient subsequently underwent a left pneumonectomy along with mediastinal lymph node dissection. Final surgical pathology of the resection specimen indicated a P‐EMC with focal high grade transformation. The patient is disease‐free 1 year post‐surgery. Conclusions: Due to the rarity of P‐EMC, insufficient sampling and histologic heterogeneity, diagnosis of P‐EMC on preoperative core needle biopsy or FNA specimen is difficult. Herein, we present a rare case of P‐EMC, with a pre‐operative FNA cytology specimen that consisted of tumor cells with dense cytoplasm and moderate cytologic atypia, strong positive staining pattern of p40, that was misdiagnosed as squamous cell carcinoma. Follow up surgical resection showed P‐EMC with focal high grade transformation. Salivary gland EMCs with high grade transformation have previously been reported to have a worse prognosis, however, little is known about the malignant potential in the lung. Next generation sequencing (NGS) using a 397‐gene solid tumor panel identified variants in DNMT3A, APC, STAT3 in both low and high grade components, while KDM5C was present only in the high grade transformation.